The roles of microbial products in the development of colorectal cancer: a review. Issue 1 (1st January 2021) - Fang, Yongkun; Yan, Cheng; Zhao, Qi; Xu, Jiaming; Liu, Zhuangzhuang; Gao, Jin; Zhu, Hanjian; Dai, Zhujiang; Wang, Daorong; Tang, Dong
ABSTRACT: A large number of microbes exist in the gut and they have the ability to process and utilize ingested food. It has been reported that their products are involved in colorectal cancer development. The molecular mechanisms which underlie the relationship between gut microbial products and CRC are still not fully understood. The role of some microbial products in CRC is particularly controversial. Elucidating the effects of gut microbiota products on CRC and their possible mechanisms is vital for CRC prevention and treatment. In this review, recent studies are examined in order to describe the contribution metabolites and toxicants which are produced by gut microbes make to CRC, primarily focusing on the involved molecular mechanisms. Abbreviations : CRC: colorectal cancer; SCFAs: short chain fatty acids; HDAC: histone deacetylase; TCA cycle: tricarboxylic acid cycle; CoA: cytosolic acyl coenzyme A; SCAD: short chain acyl CoA dehydrogenase; HDAC: histone deacetylase; MiR-92a: microRNA-92a; KLF4: kruppel-like factor; PTEN: phosphatase and tensin homolog; PI3K: phosphoinositide 3-kinase; PIP2: phosphatidylinositol 4, 5-biphosphate; PIP3: phosphatidylinositol-3, 4, 5-triphosphate; Akt1: protein kinase B subtype α; ERK1/2: extracellular signal–regulated kinases 1/2; EMT: epithelial-to-mesenchymal transition; NEDD9: neural precursor cell expressed developmentally down-regulated9; CAS: Crk-associated substrate; JNK: c-Jun N-terminal kinase; PRMT1: protein arginine methyltransferase 1; UDCA: ursodeoxycholic acid; BA: bile acids; CA: cholic acid; CDCA: chenodeoxycholic acid; DCA: deoxycholic acid; LCA: lithocholic acid; CSCs: cancer stem cells; MHC: major histocompatibility; NF-κB: NF-kappaB; GPR: G protein-coupled receptors; ROS: reactive oxygen species; RNS: reactive nitrogen substances; BER: base excision repair; DNA: deoxyribonucleic acid; EGFR: epidermal growth factor receptor; MAPK: mitogen activated protein kinase; ERKs: extracellular signal regulated kinases; AKT: protein kinase B; PA: phosphatidic acid; TMAO: trimethylamine n-oxide; TMA: trimethylamine; FMO3: flavin-containing monooxygenase 3; H2 S: Hydrogen sulfide; SRB: sulfate-reducing bacteria; IBDs: inflammatory bowel diseases; NSAID: non-steroidal anti-inflammatory drugs; BFT: fragile bacteroides toxin; ETBF: enterotoxigenic fragile bacteroides; E-cadherin: extracellular domain of intercellular adhesive protein; CEC: colonic epithelial cells; SMOX: spermine oxidase; SMO: smoothened; Stat3: signal transducer and activator of transcription 3; Th17: T helper cell 17; IL17: interleukin 17; AA: amino acid; TCF: transcription factor; CDT: cytolethal distending toxin; PD-L1: programmed cell death 1 ligand 1